Philosophical dialogue – towards the cultural history of the genre - Rakoczy, Marta (Lingua Posnaniensis, 2017)
This text analyzes philosophical dialogue (from Plato to Augustine of Hippo, Berkeley, Hume and Leibniz) as a linguistic genre embedded in the cultural, historical and media context, which was decisive for the role and functions accorded to philosophy as such. I argue that one way to describe transformations of Western thought, which has not been consistently implemented, is a description of its history through the category of progressive textualization and through anthropological-historical category of a genre. Two models of communication analyzed by Ives Winkin – orchestral and telegraphic – first associated with the perception of communication as an act of interpersonal, linguistic and non-linguistic communio, and second, the perception of communication as a linear transfer of information from one mind to another, have their historical, especially the media roots. The first is associated with the word alive and spoken communication. The second is conditioned by the primacy of the printed word and the quiet, solitary reading, which cuts off existential contexts, and decontextualizes an utterance and tranforms it into a strictly graphic message far from direct, interpersonal understanding. Both models can be seen well in philosophical texts. And the dominance of the latter, related to the development of print culture, allows us to understand why the philosophical dialogue as a trace of the conversation – a trace of the existential practice as well as philosophical – is experiencing a crisis in modern times.